2023
DOI: 10.1038/s41598-023-40521-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oxytocin on the hair growth ability of dermal papilla cells

Tatsuto Kageyama,
Jieun Seo,
Lei Yan
et al.

Abstract: Oxytocin (OXT) is a neuropeptide hormone termed “love hormone” produced and released during childbirth and lactation. It is also produced in response to skin stimulation (e.g., during hugging and massaging) and music therapy. The effects of OXT on various organs have been revealed in recent years; however, the relationship between hair follicles and OXT remains unclear. In this study, we examined the effects of OXT on dermal papilla (DP) cells that control hair growth by secreting growth/regression signals. Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…5 B). In our previous study, oxytocin caused a 1.3-increase in the same assay 6 . These results suggest that cinnamic acid has almost the same level of hair growth-promoting effect as oxytocin.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…5 B). In our previous study, oxytocin caused a 1.3-increase in the same assay 6 . These results suggest that cinnamic acid has almost the same level of hair growth-promoting effect as oxytocin.…”
Section: Discussionmentioning
confidence: 60%
“…The application of this approach to cells of human origin showed that immature hair shaft-like structures elongated in response to minoxidil, a typical hair growth-promoting agent 15 . In our previous study, we examined potential hair growth-promoting drug candidates using human hair follicloids and identified the effects of oxytocin on hair growth 6 . In the present study, we evaluated the effects of cinnamic acid (0, 50, 100 and 500 μg/mL) on hair follicles using human hair follicloids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation